Assessing translanguaging as a strategy for enhancing students’ classroom activity participations in a rural vocational high school: A case study - Karima, Kauna; Windianto, Nur Eko; Machfudi, Moch. Imam; Salsabila, Hanania; Purnawan, Ari; Sukarno, Sukarno; Yulia, Yuyun (Journal of Research on English and Language Learning (J-REaLL), 2025)
Translanguaging (TL) has been recognized for its potential to enhance students’ understanding and participation in English as a foreign language (EFL) classroom, particularly in speaking, reading, writing, and listening. This is especially relevant for vocational high school students in rural settings, where limited English proficiency and resource constraints present challenges. TL allows students to engage more actively by flexibly using their native language alongside English. However, its effectiveness depends on various contextual factors, including teachers’ implementation strategies and students’ language proficiency. This case study investigates how teachers and students perceive the effectiveness of TL in supporting comprehension within the context of English for specific purposes (ESP) in a rural school setting. The data were collected through teacher interviews, student focus group discussions, and classroom observations. Findings indicate positive perceptions of TL from both teachers and students, with teachers using it strategically to explain complex ideas and foster language skills. However, its effectiveness varies based on language familiarity, with a noted preference for mixing English with Bahasa Indonesia over Javanese. Despite TL's benefits in building confidence and comprehension, challenges such as balancing native languages with English, managing limited vocabulary, and ensuring consistent practice remain. Overall, while TL strategies could enhance comprehension and confidence in speaking English, the success depends on strategic implementation and alignment with students' proficiency levels. Future studies could explore the efficacy of TL in improving students’ comprehension across diverse educational settings.